Information and organizations - Stinchcombe, Arthur L. (Berkeley : University of California Press, 1990)
An ambitious new work by a well-respected sociologist, Information and Organizations provides a bold perspective of the dynamics of organizations. Stinchcombe contends that the "information problem" and the concept of "uncertainty" provide the key to understanding how organizations function. In a delightful mix of large theoretical insights and vivid anecdotal material, Stinchcombe explores the ins and outs of organizations from both a macro and micro perspective. He reinterprets the work of the renowned scholars of business, Alfred Chandler, James March and Oliver Williamson, and looks in depth at corporations like DuPont and General Motors. Along the way, Stinchcombe explores subjects as varied as class consciousness, innovation, contracts and university administration. All of these analyses are distinguished by incisive thinking and creative new approaches to issues that have long confronted business people and those interested in organizational theory. A tour de force, Information and Organizations is a must-read for business people and scholars of many stripes. It promises to be a widely discussed and debated work
Information, Uncertainty, Structure, and Function in Organizational Sociology -- Individuals' Skills As Information Processing: Charles F. Sabel and the Division of Labor -- Manufacturing Information Systems: Sources of Technical Uncertainty and the Information for Technical Decisions -- Market Uncertainty and Divisionalization: Alfred D. Chandler's Strategy and Structure -- Turning Inventions into Innovations: Schumpeter's Organizational Sociology Modernized -- Organizing Information Outside the Firm: Contracts As Hierarchical Documents -- Segmentation of the Labor Market and Information on the Skill of Workers -- Class Consciousness and Organizational Sociology: E.P. Thompson Applied to Contemporary Class Consciousness -- University Administration of Research Space and Teaching Loads: Managers Who Do Not Know What Their Workers Are Doing.
Includes bibliographical references (pages 363-377) and indexes.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: In'formation; Industrial sociology; Industrial organization; Organizational behavior; Management information systems; Uncertainty; Uncertainty; Management Information Systems; Sociologie industrielle; Industrie -- Organisation, contrôle, etc; Comportement organisationnel; Systèmes d'information de gestion; Incertitude; BUSINESS & ECONOMICS -- Information Management; BUSINESS & ECONOMICS -- Knowledge Capital; SOCIAL SCIENCE -- Sociology -- General; Industrial organization; Industrial sociology; Management information systems; Organizational behavior; Uncertainty; Entscheidung bei Unsicherheit; Industriebetriebslehre; Industriesoziologie; Organisation; Organisationssoziologie; Unternehmen; Managementinformationssystem; Organisationsverhalten; Organisatiegedrag; Informatiesystemen; Onzekerheid; Industrie -- Organisation, contrôle, etc; Incertitude (économie politique); Gestion d'entreprise -- Systèmes d'information.; Comportement organisationnel; Sociologie du travail